Magnetic recoverable nanoparticle anchored high-entropy catalyst as well as preparation method and application thereof

Through magnetic recovery of nanoparticle anchored high-entropy catalysts, the problems of high-concentration organic wastewater treatment methods in the prior art are solved, and low-cost and efficient organic wastewater degradation and catalysts are achieved. Long life and wide application.

CN119259072APending Publication Date: 2025-01-07WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411426951.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing high-concentration organic wastewater treatment methods have problems such as high cost, high pollution, harsh reaction conditions and unstable treatment effects. In particular, the activity, selectivity and stability of the catalyst are difficult to meet the needs of complex wastewater.

Method used

High-entropy catalysts anchored by magnetically recyclable nanoparticles are prepared by co-precipitation and calcination processes, and high-entropy metal oxides are formed using Fe, Co, Ni, Mn, and Cu elements to provide diversity and tunability to improve catalytic activity. and stability.

Benefits of technology

It realizes low-cost and efficient organic wastewater degradation. The catalyst has a long life and a wide range of applications. It can quickly treat difficult-to-degrade organic wastewater under low temperature conditions, and the catalyst can be recycled and used.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259072A_ABST
    Figure CN119259072A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic recoverable nanoparticle anchored high-entropy catalyst as well as a preparation method and application thereof, and belongs to the technical field of organic wastewater treatment. The preparation method provided by the invention adopts coprecipitation and calcination processes, and has the advantages of wide raw material source, low cost and convenient process. In the high-entropy catalyst anchored by the magnetic recoverable nanoparticles prepared based on the method, Cu is separated out from a solid solution and anchored on the surface of the high-entropy catalyst in situ to form a unique catalytic structure, and the high-entropy catalyst has high catalytic activity, selectivity and stability and is long in service life, high in treatment efficiency and wide in application range. The high-entropy catalyst anchored by the magnetic recoverable nanoparticles is applied to the field of catalytic oxidation of organic wastewater, the problems that high-concentration organic wastewater is difficult to degrade, the durability of the catalyst is poor and the like can be solved, and the high-entropy catalyst has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic wastewater treatment, and in particular to a magnetically recyclable nanoparticle-anchored high-entropy catalyst and a preparation method and application thereof. Background Art

[0002] High-concentration organic wastewater refers to wastewater containing a large amount of organic matter that is difficult to biodegrade, such as chemical wastewater, dye wastewater, pharmaceutical wastewater, etc. These wastewaters usually have complex chemical composition, high chemical oxygen demand, high chroma, high toxicity and odor, etc., which cause serious harm to the environment and human health. Therefore, the treatment of high-concentration organic wastewater is an environmental problem that needs to be solved urgently.

[0003] At present, the commonly used methods for treating high-concentration organic wastewater mainly include physical methods, chemical methods and biological methods. Physical methods mainly include adsorption, membrane separation, electrolysis, etc. Although these methods can effectively remove organic matter in wastewater, they will produce a large amount of sludge or concentrated liquid, which requires further treatment, increasing the cost and difficulty of treatment. Chemical methods mainly include oxidation, reduction, chlorination, etc. Although these methods can convert organic matter into harmless substances, they will consume a large amount of chemical reagents, produce secondary pollution, and the reaction conditions are relatively harsh. Biological methods mainly include aerobic methods, anaerobic methods, aerobic-anaerobic methods, etc. Although these methods can utilize the metabolism of microorganisms to degrade organic matter, they are affected by factors such as the type, concentration, temperature, and pH of organic matter in wastewater. The reaction rate is slow, the treatment effect is unstable, and the treatment effect on difficult-to-biodegrade organic matter is poor.

[0004] In order to overcome the shortcomings of the above methods, catalytic oxidation has received extensive attention and research in recent years as a new type of high-concentration organic wastewater treatment method. Catalytic oxidation is a method of oxidizing organic matter in wastewater into carbon dioxide and water using a catalyst under a certain temperature, pressure and oxygen or air, including photocatalytic oxidation, wet catalytic oxidation, supercritical water oxidation, electrocatalytic oxidation, chemical catalytic oxidation, etc. This method has the advantages of fast reaction rate, good treatment effect, no secondary pollution, and mild operating conditions. The key to catalytic oxidation is the selection and design of the catalyst. The activity, selectivity and stability of the catalyst directly affect the efficiency and cost of the catalytic oxidation reaction.

[0005] At present, commonly used catalytic oxidants mainly include precious metal catalysts, transition metal oxide catalysts, multi-metal oxide catalysts, etc. Precious metal catalysts such as Pt, Pd, Rh, etc. have high catalytic activity, but they are expensive, easily poisoned by impurities in wastewater, and have certain harm to the environment. Transition metal oxide catalysts such as Fe, Co, Ni, Mn, Cu, etc. have the advantages of low price, catalytic stability, and environmental friendliness, but have low catalytic activity and are easily limited by thermodynamics and kinetics. Multi-metal oxide catalysts are composite catalysts composed of two or more transition metal oxides, such as Fe-Mn, Co-Mn, Ni-Mn, etc., which have high catalytic activity, but due to the molar ratio of metal elements, the structure and morphology are not uniform, resulting in unstable performance of the catalyst and difficult to control.

[0006] High entropy metal oxides refer to single-phase or multiphase solid solutions composed of five or more elements in approximately equal or unequal molar ratios, with unique microstructures, excellent thermal stability and catalytic activity for various reactions. High entropy metal oxides can be used to oxidize organic matter in wastewater into carbon dioxide and water by catalytic oxidation technology to achieve the purpose of removal; they are expected to be used to treat high-concentration organic wastewater, such as chemical wastewater, dye wastewater, pharmaceutical wastewater, etc. High entropy metal oxides can be synthesized by gas phase, liquid phase or solid phase reaction, such as carbon thermal shock method, fast moving bed pyrolysis method, electric shock method, etc. However, the synthesis conditions of high entropy metal oxides are harsh, and their crystal structure, electronegativity and coordination number balance should be comprehensively considered during preparation. The crystal structures of high entropy metal oxides mainly include rock salt type, fluorite type, perovskite type and spinel type. The diverse crystal structures have further increased the application potential of high entropy metal oxides in different catalytic fields, but also increased the difficulty of application in the target catalytic field.

[0007] In summary, designing and providing a high entropy metal oxide catalyst and its preparation process to meet the requirements of high catalytic activity, selectivity and stability, and adapt to the diversity and complexity of wastewater treatment, and to achieve efficient degradation and harmless treatment of wastewater, is of positive significance for solving the environmental problems caused by wastewater. Summary of the invention

[0008] In view of the above-mentioned defects of the prior art, in a first aspect of the present invention, a method for preparing a high-entropy catalyst anchored by magnetic recyclable nanoparticles with low cost and convenient process is provided, comprising the following steps: (1) dissolving a water-soluble metal salt in water to form a metal salt solution; Among them, the water-soluble metal salts include metal salts of iron (III), metal salts of cobalt (II), metal salts of nickel (II), metal salts of manganese (II), and metal salts of copper (II); (2) adding the metal salt solution dropwise to the aqueous solution of the precipitant to form a coprecipitation suspension; (3) The coprecipitated suspension is recovered, purified, and dried to obtain a precursor; (4) The precursor is calcined to obtain a high-entropy catalyst anchored by magnetic recyclable nanoparticles.

[0009] Preferably, in step (1), in the water-soluble metal salt, the molar ratio of the metal elements is Co:Fe:Ni:Mn:Cu=1.0-1.5:1.0-1.5:1.0-1.5:1.0-1.5:1.0-1.5.

[0010] Preferably, in step (1), the water-soluble metal salt includes at least one of metal nitrates, metal chlorides, metal acetates and hydrates thereof.

[0011] Preferably, in step (1), the concentration of the metal elements in the metal salt solution is independently 0.01-1 mol / L.

[0012] Depending on the type of metal ions in the metal salt solution, the choice of precipitant is diverse. Those skilled in the art can select salts or compounds with good water solubility and ionization to produce hydroxide ions based on actual conditions. For example, NaOH, Na2CO3, NaHCO3, NH3·H2O, etc. are particularly suitable for the present invention because of their wide sources and low cost.

[0013] Preferably, in step (2), the precipitant includes at least one of NaOH, Na2CO3, NaHCO3, and NH3·H2O.

[0014] Excessive precipitant may lead to too fast precipitation reaction, causing the crystal nucleus to grow too fast during the precipitation process, resulting in particle agglomeration. Such agglomeration phenomenon will reduce the specific surface area and is not conducive to the subsequent catalytic reaction. When the precipitation process is too fast, it is difficult to control the co-precipitation rate of each metal ion, which may lead to an imbalance in the precipitation ratio between the metal ions and cause the final high entropy metal oxide composition to deviate from expectations. If the precipitant dosage is insufficient, the pH value of the solution may not reach the range of co-precipitation of all metal ions, and some metal ions cannot be completely precipitated, resulting in incomplete precipitated metal components. In this way, the target high entropy metal oxide may not be formed or formed incompletely during the subsequent calcination process. Due to incomplete precipitation of metal ions, some metal components in the final high entropy metal oxide will be missing, resulting in a decrease in the diversity of the catalyst and the number of active sites, affecting the catalytic performance. Insufficient precipitant dosage may also lead to uneven distribution of different metal ions in the generated precipitate. In the subsequent calcination process, this inhomogeneity will lead to an uneven high entropy solid solution structure, affecting the physical and chemical properties of the material.

[0015] Preferably, in step (2), the concentration of the precipitant in the aqueous solution of the precipitant is 0.01-1 mol / L.

[0016] Preferably, the specific operation of step (3) comprises the following steps: centrifuging the coprecipitation suspension and collecting the precipitate, washing the precipitate with water until the pH is neutral, and then removing the water by freeze drying to obtain the precursor.

[0017] Further preferably, the freeze-drying time is 24-48 h.

[0018] Appropriate calcination temperature helps to optimize the crystallinity of high entropy materials and give them better catalytic performance. Too high or too low calcination temperature will result in a decrease in the target diffraction peak of the crystal. Too high or too low calcination temperature will reduce the content of in-situ precipitated Cu and high entropy substrate, and the crystal form is poor.

[0019] Preferably, in step (4), the calcination temperature is 800-1200°C and the calcination time is 1-3 h.

[0020] In the second aspect of the present invention, a high-entropy catalyst anchored by magnetically recyclable nanoparticles is provided, which has high catalytic activity, selectivity and stability, long service life, high processing efficiency and wide application range, and is prepared by the preparation method of the first aspect of the present invention.

[0021] In the third aspect of the present invention, there is provided an application of the high entropy catalyst anchored by magnetically recoverable nanoparticles according to the second aspect of the present invention, specifically, an application as a catalyst in catalytic oxidation treatment of organic wastewater.

[0022] The catalyst of the present invention has the advantage of wide application and has excellent treatment effect on various types of organic wastewater. Organic wastewater is not limited to antibiotic wastewater, etc., but also includes printing and dyeing wastewater, pharmaceutical wastewater and other difficult-to-degrade organic wastewater.

[0023] Preferably, the application method comprises the following steps: adding a high entropy catalyst anchored by magnetic recyclable nanoparticles and an oxidant to the organic wastewater to be treated, and performing catalytic oxidation at a reaction temperature.

[0024] Further preferably, based on the proportion of the components in the organic wastewater, the dosage of the high entropy catalyst anchored by the magnetic recyclable nanoparticles is ≤4 g / L; the oxidant is H2O2, and the dosage of the oxidant is 0.02-0.10 mol / L.

[0025] The high entropy catalyst anchored by magnetic recyclable nanoparticles has good low-temperature reducibility and can treat high-concentration difficult-to-degrade organic wastewater with fast catalytic oxidation efficiency at 30-50°C.

[0026] More preferably, the reaction temperature is 30-50 °C.

[0027] In order to overcome the shortcomings of the existing catalytic system, based on the above technical scheme, the design concept and principle of the present invention is to design a new type of high-entropy metal oxide catalyst with Fe, Co, Ni, Mn, and Cu, which are widely available and low-cost, and utilize the diversity and adjustability of the high-entropy metal oxide catalyst to improve the activity, selectivity and stability of the catalyst to adapt to the diversity and complexity of wastewater treatment, thereby achieving efficient degradation and harmless treatment of wastewater.

[0028] The magnetically recyclable nanoparticle-anchored high entropy catalyst (hereinafter referred to as high entropy catalyst) of the present invention can be denoted as Cu 0 NPs@Co-HEOs high entropy catalyst (Cu 0 NPs are surface-anchored Cu nanoparticles, and Co-HEOs are matrix Co-based spinel high entropy oxides). The high entropy catalyst contains active metal oxide components of Fe, Co, Ni, Mn and Cu. The active components form a high entropy solid solution under high temperature conditions, thereby forming a heterogeneous structure. The heterogeneous structure not only provides a variety of active sites during the catalytic process, but also significantly improves the catalytic effect through defect structures, oxygen vacancies and high thermal stability. It is worth noting that Cu precipitates from the solid solution during high-temperature calcination and in-situ anchors on the surface of the high entropy catalyst to form nanoparticles by agglomeration. The in-situ precipitation and anchoring of Cu promotes the activation efficiency of the oxidant H2O2, thereby further improving the catalytic performance of the catalyst. The catalyst has achieved good application results in the activation of H2O2 in an intermittent catalytic ultrafast oxidation reactor to treat various types of organic wastewater.

[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention provides a method for preparing a high-entropy catalyst anchored by magnetic recyclable nanoparticles, which adopts a co-precipitation and calcination process and has the advantages of a wide source of raw materials, low cost and a convenient process.

[0030] The invention provides a magnetically recyclable nanoparticle-anchored high-entropy catalyst, wherein Cu is precipitated from a solid solution and in-situ anchored on the surface of the high-entropy catalyst to form a unique catalytic structure, which has high catalytic activity, selectivity and stability, a long service life, high processing efficiency and a wide range of applications.

[0031] The present invention provides an application of a high-entropy catalyst anchored by magnetic recyclable nanoparticles, which has good application prospects in the field of oxidation catalysis of organic wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a comparison chart of the removal rate of sulfadiazine (SDZ) in antibiotic wastewater by different catalysts; Figure 2 This is a comparison chart of the removal rate of SDZ in antibiotic wastewater by high entropy catalysts prepared under different calcination temperature conditions; Figure 3 This is a comparison chart of SDZ removal efficiency in antibiotic wastewater by high entropy catalyst under different reaction temperature conditions; Figure 4 This is a comparison chart of SDZ removal efficiency in antibiotic wastewater under different dosage conditions of high entropy catalyst; Figure 5 This is a comparison chart of SDZ removal efficiency in antibiotic wastewater by high entropy catalyst under different oxidant dosage conditions; Figure 6 This is a comparison chart of SDZ removal efficiency in antibiotic wastewater by high entropy catalysts at different initial pollutant concentrations; Figure 7 This is a comparison chart of the removal rates of different pollutants in antibiotic wastewater by high entropy catalysts; Figure 8 This is the effect diagram of the cycle test of SDZ antibiotic wastewater degradation after the stability test of the high entropy catalyst; Fig. 9 It is the hysteresis loop spectrum of high entropy catalyst; Fig.10 X-ray diffraction (XRD) pattern of the high entropy catalytic agent; Fig.11 This is a scanning electron microscope (SEM) image of a high entropy catalyst; Fig.12 This is a transmission electron microscope (TEM) image of a high-entropy catalyst; Fig.13 Electron paramagnetic resonance (EPR) images for free radical generation detection of high entropy catalysts; Fig.14 is the XRD pattern of the high entropy catalyst; Fig.15 For H2O2 molecules in Cu 0 Gibbs free energy of dissociation, adsorption and fragmentation of different metal sites of NPs@Co-HEOs; Fig.16 is the charge displacement curve on the surface Cu site and the native metal site; Fig.17 is the local integral curve of the differential density between the surface Cu site and the native metal site; Fig.18 Cu 0 Partial density of states (PDOS) plots and d-band centers of Cu, Co, Fe, Mn, and Ni of NPs@Co-HEOs. DETAILED DESCRIPTION

[0033] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0034] Example 1 The high entropy catalyst anchored by magnetic recyclable nanoparticles of this embodiment is prepared by the following steps: (1) According to the element requirements, a certain amount of Fe(NO3)3·9H2O (4.04 g), Co(NO3)2·6H2O (2.91 g), Ni(NO3)2·6H2O (2.91 g), Mn(NO3)2·4H2O (2.51 g) and Cu(NO3)2·3H2O (2.42 g) were stirred and dissolved in 100 mL of distilled water in an equimolar ratio to form a metal salt solution; (2) Dissolve NaOH (4.00 g) in 100 mL of distilled water to obtain an aqueous solution of the precipitant; add the metal salt solution dropwise to the aqueous solution of the precipitant and stir continuously with a glass rod to form a coprecipitation suspension; (3) centrifuging the coprecipitated suspension, repeatedly washing the precipitate with pure water until the pH is neutral or nearly neutral, and then drying in a freeze dryer to remove water to obtain a precursor; (4) The precursor was placed in a muffle furnace and calcined at 1000 °C for 2 h (heating rate of 5 °C / min), cooled in the furnace and taken out to obtain a magnetic recyclable nanoparticle-anchored high entropy catalyst, denoted as CFNMC (CoFeNiMnCuO x The metal initials of the letter (the same below).

[0035] This embodiment is based on high entropy catalyst, according to Co a Fe b Ni c Mn d Cu e O xThe elemental composition of the catalyst (a, b, c, d, e can all be 0) was controlled by the same method to prepare four catalysts CoO x 、CoFeO x 、CoFeNiO x 、CoFeNiMnO x , used for research and comparison; and are recorded as C, CF, CFN, and CFNM respectively.

[0036] This example studies the catalytic performance of high entropy catalyst (CFNMC) anchored by magnetic recyclable nanoparticles and C, CF, CFN, and CFNM in practical applications. The prepared catalysts were respectively used in an intermittent catalytic ultrafast oxidation reactor to treat antibiotic wastewater (C SDZ =15 mg / L) for treatment, where the reaction conditions are: reaction temperature of 45 ℃, catalyst dosage of 4 g / L, oxidant (H2O2) dosage of 0.06 mol / L. The comparison of SDZ removal rate of different catalysts in antibiotic wastewater is shown in the figure Figure 1 As shown; the removal rates of SDZ in antibiotic wastewater by different catalysts at different times are shown in Table 1.

[0037] Table 1: Removal rate of SDZ in antibiotic wastewater by different catalysts at different times

[0038] As shown in the above test results, the catalyst has a significant improvement in the removal rate of SDZ in antibiotic wastewater. When the high entropy state is reached, the removal rate of SDZ in antibiotic wastewater by the prepared high entropy catalyst reaches more than 99%.

[0039] Example 2 This example studies the effect of calcination temperature on the performance of high entropy catalyst anchored by magnetic recyclable nanoparticles. The preparation method of this example is basically the same as that of Example 1, except that the calcination temperature is different. In this example, the corresponding high entropy catalysts were prepared at 800 °C, 900 °C, 1100 °C, and 1200 °C. The prepared high entropy catalyst was used in an intermittent catalytic ultrafast oxidation reactor to treat antibiotic wastewater (C SDZ =15 mg / L) was used for treatment, where the reaction conditions were: reaction temperature of 45 °C, catalyst dosage of 4 g / L, and oxidant (H2O2) dosage of 0.06 mol / L. The comparison of SDZ removal efficiency of high entropy catalysts prepared under different calcination temperature conditions in antibiotic wastewater is shown in the figure. Figure 2 As shown; the removal rate of SDZ in antibiotic wastewater by high entropy catalysts prepared at different calcination temperatures at different times is shown in Table 2.

[0040] Table 2: Removal efficiency of SDZ in antibiotic wastewater by high entropy catalysts prepared at different calcination temperatures at different times

[0041] As shown in the above test results, when the final prepared catalyst is used, the removal rate of SDZ in antibiotic wastewater reaches more than 99%. Compared with other calcination temperatures, the high entropy catalyst prepared by calcination at 1000 °C can achieve a higher removal rate more quickly.

[0042] Example 3 This example studies the high entropy catalyst prepared in Example 1 in an intermittent catalytic ultrafast oxidation reactor for the treatment of antibiotic wastewater (C SDZ =15 mg / L) was treated with the high entropy catalyst at different reaction temperatures, and the effects of different reaction temperatures on SDZ removal were compared. The reaction conditions were: reaction temperature of 30-50 °C, catalyst (H2O2) dosage of 4 g / L, and oxidant dosage of 0.06 mol / L. The comparison of SDZ removal rates of high entropy catalysts in antibiotic wastewater under different reaction temperature conditions is shown in the figure below. Figure 3 As shown; the removal rate of SDZ in antibiotic wastewater by high entropy catalyst at different reaction temperatures and different times is shown in Table 3.

[0043] Table 3: Removal efficiency of SDZ in antibiotic wastewater by high entropy catalyst at different reaction temperatures and time

[0044] As shown in the above test results, with the increase of reaction temperature, the removal rate of SDZ shows an increasing trend, and the high entropy catalyst can achieve a higher catalytic efficiency in a shorter time. The removal rate of SDZ in antibiotic wastewater by high entropy catalyst at 50 ℃ for 30 min reached 99.59%.

[0045] Example 4 This example studies the application performance of the high entropy catalyst prepared in Example 1 when different dosages are added, and compares the effects of different catalyst dosages on SDZ removal efficiency. The prepared high entropy catalyst is used in an intermittent catalytic ultrafast oxidation reactor to treat antibiotic wastewater (C SDZ =15 mg / L) for treatment, where the reaction conditions are: reaction temperature of 45 ℃, catalyst dosage of 0-4 g / L, oxidant (H2O2) dosage of 0.06 mol / L. The comparison of SDZ removal rate of high entropy catalyst in antibiotic wastewater under different dosage conditions is shown in the figure Figure 4 As shown; the removal rate of SDZ in antibiotic wastewater at different times with different high entropy catalyst dosages is shown in Table 4.

[0046] Table 4: Removal rate of SDZ in antibiotic wastewater at different times with different high entropy catalyst dosages

[0047] As shown in the above test results, in the absence of a catalyst, the SDZ removal rate was extremely low; when the catalyst dosage increased from 1 g / L to 4 g / L, the SDZ degradation rate increased from 33.04% to 99.59% within 60 min.

[0048] Example 5 This example studies the effect of the high entropy catalyst prepared in Example 1 on the SDZ removal rate under different oxidant (H2O2) dosages. The prepared high entropy catalyst was used in an intermittent catalytic ultrafast oxidation reactor to treat antibiotic wastewater (C SDZ =15 mg / L) for treatment, where the reaction conditions are: reaction temperature of 45 °C, catalyst dosage of 4 g / L, oxidant (H2O2) dosage of 0.02-0.10 mol / L. The comparison of SDZ removal rate of high entropy catalyst in antibiotic wastewater under different oxidant dosage conditions is shown in the figure below. Figure 5 As shown; the removal rate of SDZ in antibiotic wastewater by high entropy catalyst at different oxidant dosages at different times is shown in Table 5.

[0049] Table 5: Removal rate of SDZ in antibiotic wastewater by high entropy catalyst at different oxidant dosages at different times

[0050] As shown in the above test results, with the increase of the dosage of oxidant (H2O2), the removal rate of SDZ gradually increased; when the dosage of oxidant (H2O2) was 0.06 mol / L, the removal rate of SDZ was as high as 99.57% within 30 min.

[0051] Example 6 This example studies the performance of the high entropy catalyst prepared in Example 1 under different conditions of initial pollutant concentrations, and compares the effects of different initial pollutant concentrations on the SDZ removal rate. The prepared high entropy catalyst was used to treat antibiotic wastewater in an intermittent catalytic ultrafast oxidation reactor, wherein the reaction conditions were: reaction temperature of 45°C, catalyst dosage of 4 g / L, and oxidant (H2O2) dosage of 0.06 mol / L. The comparison of the SDZ removal rate of the high entropy catalyst in antibiotic wastewater under different initial pollutant concentrations is shown in the figure below. Figure 6 As shown; the removal rate of SDZ in antibiotic wastewater by high entropy catalyst at different initial pollutant concentrations at different times is shown in Table 6.

[0052] Table 6: Removal efficiency of SDZ in antibiotic wastewater by high entropy catalyst at different initial pollutant concentrations at different times

[0053] As shown in the test results above, when the initial SDZ concentration increased from 5 mg / L to 25 mg / L, the maximum SDZ removal was achieved at an initial concentration of 15 mg / L within 20 min, and the SDZ removal rate was 99.35%.

[0054] Example 7 This example studies the degradation performance of the high entropy catalyst prepared in Example 1 when used for different pollutants to be degraded. The types of pollutants include SDZ, sulfamethoxazole (SMX), moxifloxacin (MOX), ciprofloxacin (CIP), gefitinib (GEF) and methotrexate (MTX), and the effects of high entropy catalysts on the removal efficiency of different pollutants are compared. The prepared high entropy catalyst was used to treat antibiotic wastewater (C=15 mg / L) in an intermittent catalytic ultrafast oxidation reactor, wherein the reaction conditions are: reaction temperature of 45 °C, catalyst dosage of 4 g / L, and oxidant (H2O2) dosage of 0.06 mol / L. The comparison of the removal rates of different pollutants in antibiotic wastewater by high entropy catalysts is shown in the figure below. Figure 7 As shown; the removal rates of different pollutants in antibiotic wastewater by high entropy catalyst at different times are shown in Table 7.

[0055] Table 7: Removal rate of different pollutants in antibiotic wastewater by high entropy catalyst at different times

[0056] As shown in the test results of Table 7, the high entropy catalyst degradation system has a wide range of applications and has a rapid removal effect on a variety of pollutants. Therefore, the catalytic ultrafast oxidation treatment method of the high entropy catalyst provided in the present application has wide adaptability and flexibility, and can treat different types of organic wastewater under different application scenarios and conditions.

[0057] Example 8 In this example, the high entropy catalyst prepared in Example 1 was used to oxidize antibiotic wastewater (C SDZ=15 mg / L) was used for treatment, where the reaction conditions were: reaction temperature of 45 °C, catalyst dosage of 4 g / L, and oxidant (H2O2) dosage of 0.06 mol / L. The stability of the high entropy catalyst on the catalytic degradation of SDZ was evaluated by cyclic testing. After the stability test of the high entropy catalyst, the cyclic test effect of the degradation of SDZ antibiotic wastewater is shown in the figure Figure 8 As shown; the cyclic test results of the high entropy catalyst are shown in Table 8.

[0058] Table 8: Cyclic test results of high entropy catalysts

[0059] As shown in the test results above, the high entropy catalyst can still achieve a high SDZ removal efficiency even after 8 consecutive cycles. In addition, the catalyst activity did not decrease significantly throughout the test, and the SDZ removal efficiency was stable at more than 95.6% within 20 minutes. These findings indicate that the catalytic activity of the high entropy catalyst remains stable over time, the catalyst has good stability in the reaction, and is not easily passivated by reaction conditions or pollutants.

[0060] Example 9 The high entropy catalyst used in Example 3 was subjected to hysteresis loop detection. The hysteresis loop spectrum is shown in Fig. 9 The vibrating sample magnetometer used in the hysteresis loop detection is manufactured by LakaShore, USA, model 7404 / 8604. Fig. 9 As shown, in an external magnetic field of -20000-20000 Oe, the S-curve of the high entropy catalyst indicates that it has superparamagnetism, and its calculated saturation magnetization intensity (18.53 emu / g) is higher than the magnetic separation limit (16.3 emu / g), which means that it can be easily collected from water with an external magnet, achieving rapid separation and repeated use.

[0061] Example 10 The high entropy catalyst used in Example 3 was subjected to X-ray diffraction detection. The XRD pattern is shown in Fig.10 ; Among them, the manufacturer of the X-ray diffractometer used for X-ray diffraction detection is Bruker AXS of Germany, and the model is Bruker D8Advance. Fig.10 As shown, the high entropy catalyst used in Example 3 shows a spinel structure composed of cubic phase Cu 0 (PDF#70-3038) and Co-HEOs (PDF#80-1540) without any third phase, further demonstrating the successful preparation of high entropy catalysts and their unique nanoparticle anchoring structure.

[0062] Embodiment 11 The high entropy catalyst used in Example 3 was examined by scanning electron microscopy. The SEM images are shown in Fig.11 The scanning electron microscope used in the scanning electron microscope test was manufactured by Carl Zeiss of Germany, and its model is GeminiSEM 300. Fig.11 As shown, the surface of the high entropy catalyst is covered with many dense and evenly distributed nano-clustered particles, which are active components composed of high entropy metal oxides. This further proves that the high entropy catalyst used in Example 3 has a higher active site density, which helps to improve the processing efficiency of the high entropy catalyst in catalyzing ultrafast oxidation.

[0063] Example 12 The high entropy catalyst used in Example 3 was tested by transmission electron microscopy. The TEM image is shown in Fig.12 The transmission electron microscope used in the transmission electron microscope test was manufactured by FEI of the United States and its model was Tecnai G2 F20. Fig.12 As shown, the lattice spacing is 4.85 Å, which is similar to the lattice spacing of 4.66 Å of the Co3O4 unit cell (1 1 1) crystal plane, which proves that the catalyst is a single cubic phase based on the Co3O4 unit cell and belongs to the Co-based spinel high entropy metal oxide. There are also many agglomerated nanoparticles on the catalyst surface, with an average size of less than 6 nm. The lattice spacing of the nanoparticles is 2.10 Å, which is similar to the lattice spacing of 2.08 Å of the single Cu unit cell (1 1 1) crystal plane, which proves that the nanoparticles on the surface are Cu 0 .

[0064] Therefore, the surface of the high entropy catalyst prepared in this application is anchored with nanoparticles of Cu 0 , and this structure can promote the activation rate of the catalyst to H2O2 and improve the catalytic performance and stability of the catalyst.

[0065] Embodiment 13 The element content of the high entropy catalyst used in Example 3 was detected, and the detection results are shown in Table 9; wherein the wavelength dispersive X-ray fluorescence spectrometer used for element content detection was manufactured by Rigaku Corporation of Japan, and the model number was ZSXPrimus IV.

[0066] Table 9: Element content test results of high entropy catalyst

[0067] According to the results in Table 9, the ratio of the content of each metal element in the high entropy catalyst used in Example 3 is Co:Fe:Ni:Mn:Cu=1.3:1.2:1.1:1.2:1.4. At this time, the ratio of the content of the five metal elements is approximately equal to a certain extent, and the metal element content of the surface active component is basically consistent with the catalyst preparation situation, indicating that there is no obvious loss or separation of the metal elements during the preparation process.

[0068] Embodiment 14 The element content of the surface of the high entropy catalyst used in Example 3 was detected, and the detection results are shown in Table 10; wherein, the manufacturer of the energy spectrometer detector used for the surface element content detection is ZEISS of Germany, and the model is GeminiSEM 300.

[0069] Table 10: Surface element content test results of high entropy catalysts

[0070] According to the results in Table 10, except for Cu, various elements are evenly distributed on the catalyst surface without obvious detachment or aggregation. The loading amount of active components is approximately equimolar, which is basically consistent with the preparation of the catalyst. However, the surface Cu element agglomerates and has a high content, indicating that the Cu element in the material is precipitated during calcination and anchored on the surface to form nanoparticles.

[0071] Embodiment 15 The high entropy catalyst used in Example 3 was tested for free radical generation, and the EPR image is shown in Fig.13 The paramagnetic resonance spectrometer used for free radical generation detection was manufactured by Bruker of Germany, and its model number was EMXplus-6 / 1. Fig.13 As shown in Figure 2, only a featureless EPR response was produced at 0 min, while after heating for 20 min, clear DMPO-·OH adducts and DMPO-O2 can be observed in the range of 3480 to 3540 G. - In contrast, the corresponding signal after heating is significantly stronger than that without heating, which also indicates that the new high entropy catalyst can effectively enhance the activation of H2O2 to produce ·OH radicals and ·O2 under heating conditions. - Free radicals.

[0072] Example 16 The high entropy catalysts prepared at different calcination temperatures in Example 2 were characterized by X-ray diffraction. The corresponding XRD patterns are as follows: Fig.14 The X-ray diffraction pattern of the material powder prepared by this method shows that it has a uniform spinel structure, which is composed of cubic phase Cu 0(PDF#70-3038) and Co-HEOs (PDF#80-1540) without any third phase. The high entropy catalytic material calcined at 1000 °C has a strong diffraction peak, indicating that the high entropy material calcined at this temperature has good crystallinity and good catalytic performance. Too high or too low calcination temperature will lead to a decrease in the diffraction peak, indicating that the in-situ precipitated Cu and high entropy substrate content formed by too high or too low calcination temperature are reduced, and the crystal form is poor.

[0073] Embodiment 17 In this example, in order to further reveal the high entropy catalyst Cu 0 The specific details of the H2O2 activation process in NPs@Co-HEOs were comprehensively calculated by density functional theory, and the possible reaction pathways for the formation of active species on the surface Cu site, native Cu site and other native metal sites were comprehensively calculated. Fig.15 The Gibbs free energy step diagram of all intermediates in the reaction path was calculated as shown in the figure. The adsorption energies on the surface Cu site and other native metal sites are -0.84 eV, 0.30 eV, 0.23 eV, 0.01 eV, 0.11 eV and 0.25 eV, respectively, indicating that the adsorption of H2O2 molecules on the surface Cu site is spontaneous. In addition, the adsorption energies of H2O2 fragmentation to form adsorbed *OH and free ·OH on the surface Cu site and other native metal sites are -1.96 eV, 0.80 eV, -0.57 eV, 1.61 eV, 0.08 eV and 0.32 eV, respectively, indicating that the surface Cu site is more conducive to the formation of adsorbed *OH and free ·OH.

[0074] Fig.16 The differential density charge diagram and electron density redistribution diagram of H2O2 adsorbed on the surface Cu site and the native metal site clearly show that the electrons between the catalyst and H2O2 are transferred from the metal site to H2O2. 0 In NPs@Co-HEOs, the charge transfer of H2O2 to the surface Cu site is greater than that to other metal sites, indicating that Cu 0 NPs@Co-HEOs (surface Cu sites) have good affinity and strong interaction adsorption energy for H2O2. Compared with the native metal sites, the surface Cu sites show obvious electron density redistribution, indicating the existence of obvious charge transfer, which may be crucial for the activation of H2O2, promoting the polarization of H2O2 molecules, weakening the OO bond, accelerating the dissociation to generate ·OH, and making the surface Cu sites the main active centers in the catalytic reaction.

[0075] Fig.17The integral plot of the differential density charge reveals local changes in the electronic structure, further confirming that the surface Cu site effectively changes the charge distribution around the adsorbed H2O2, enabling its activation. The differential density charge integrals of other native metal sites are less obvious, indicating less electron redistribution therein, and the weak charge transfer suggests that the native metal sites play a smaller role in the catalytic activation of H2O2.

[0076] In order to reveal this mechanism in depth at the atomic level, Fig.18 The PDOS of each element including Cu, Co, Fe, Mn and Ni of the catalyst is displayed. It can be seen that the PDOS value near the Fermi level (Ef) is not 0, indicating that there are free electrons in the catalyst material. These electrons can participate in electron transfer and catalytic reactions, have good electron transfer characteristics and catalytic activity, and are conducive to the adsorption and dissociation of the catalyst surface. Fig.18 The d-band centers of Cu, Co, Fe, Mn, and Ni sites are also shown, with the center of Cu at -2.86 eV, and the centers of the other metals at -4.49 eV, -4.71 eV, -4.34 eV, and -3.44 eV, respectively. In general, the closer the d-band center is to the Fermi level, the stronger the adsorption of the intermediate. Therefore, the stronger the adsorption of Cu on the reaction intermediate, the more obvious it is. This indicates that the defective oxygen vacancies accept the electrons of the Cu 3d orbital, leading to the delocalization of the electrons at the surface Cu sites, thereby promoting the adsorption of the H2O2 / ·OH intermediate onto the oxygen vacancy structure. Computational analysis shows that the catalyst Cu 0 The surface Cu sites in NPs@Co-HEOs play a major role in the adsorption and activation of H2O2, and other sites provide transfer electrons to the surface Cu sites, allowing the high-entropy reaction to proceed continuously.

[0077] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing a high entropy catalyst anchored by magnetically recyclable nanoparticles, characterized in that: The steps include: (1) dissolving a water-soluble metal salt in water to form a metal salt solution; Among them, the water-soluble metal salts include metal salts of iron (III), metal salts of cobalt (II), metal salts of nickel (II), metal salts of manganese (II), and metal salts of copper (II); (2) adding the metal salt solution dropwise to the aqueous solution of the precipitant to form a coprecipitation suspension; (3) The coprecipitated suspension is recovered, purified, and dried to obtain a precursor; (4) The precursor is calcined to obtain a high-entropy catalyst anchored by magnetic recyclable nanoparticles.

2. The method for preparing a high entropy catalyst anchored by magnetic recyclable nanoparticles according to claim 1, characterized in that: In the step (1), in the water-soluble metal salt, the molar ratio of metal elements is Co:Fe:Ni:Mn:Cu=1.0-1.5:1.0-1.5:1.0-1.5:1.0-1.5:1.0-1.5; the water-soluble metal salt includes at least one of metal nitrates, metal chlorides, metal acetates and hydrates thereof.

3. The method for preparing a high entropy catalyst anchored by magnetic recyclable nanoparticles according to claim 1, characterized in that: In the step (1), the concentration of the metal elements in the metal salt solution is independently 0.01-1 mol / L.

4. The method for preparing a high entropy catalyst anchored by magnetic recyclable nanoparticles according to claim 1, characterized in that: In the step (2), the precipitant includes at least one of NaOH, Na2CO3, NaHCO3, and NH3·H2O; and the concentration of the precipitant in the aqueous solution of the precipitant is 0.01-1 mol / L.

5. The method for preparing a high entropy catalyst anchored by magnetic recyclable nanoparticles according to claim 1, characterized in that: The specific operation of step (3) comprises the following steps: centrifuging the coprecipitation suspension and collecting the precipitate, washing the precipitate with water until the pH is neutral, and then removing the water by freeze drying to obtain the precursor.

6. The method for preparing a high entropy catalyst anchored by magnetic recyclable nanoparticles according to claim 1, characterized in that: In the step (4), the calcination temperature is 800-1200°C and the calcination time is 1-3 h.

7. A magnetically recyclable nanoparticle-anchored high entropy catalyst, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 6.

8. An application of the magnetically recyclable nanoparticle-anchored high entropy catalyst as claimed in claim 7, characterized in that: Application as a catalyst in catalytic oxidation treatment of organic wastewater.

9. The use according to claim 8, characterized in that: The application method comprises the following steps: adding a high entropy catalyst anchored by magnetic recyclable nanoparticles and an oxidant into the organic wastewater to be treated, and performing catalytic oxidation at a reaction temperature.

10. The use according to claim 9, characterized in that: Calculated by the proportion of the components in the organic wastewater, the dosage of the high entropy catalyst anchored by the magnetic recyclable nanoparticles is ≤4 g / L; the oxidant is H2O2, and the dosage of the oxidant is 0.02-0.10 mol / L; the reaction temperature is 30-50°C.

Citation Information

Cited By

  • Method for treating sludge through subcritical oxidation method

    CN119841520A